2021
DOI: 10.1002/hipo.23329
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in the hippocampus and amygdala of behaviorally inhibited macaque monkeys

Abstract: Behavioral inhibition is a temperamental disposition to react warily when confronted by unfamiliar people, objects, or events. Behaviorally inhibited children are at greater risk of developing anxiety disorders later in life. Previous studies reported that individuals with a history of childhood behavioral inhibition exhibit abnormal activity in the hippocampus and amygdala. However, few studies have investigated the struc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
0
6
0
1
Order By: Relevance
“…In previous studies, we found that DU20 and ST36 are frequently used acupuncture points for the treatment of ischemic cerebrovascular diseases [19]. Therefore, we selected these two acupoints as the targets of electroacupuncture in this experiment [18,20]. Our MWM results showed that the time it took for the electroacupuncture group to find a platform in the place navigation test was significantly shorter than that of the VaD group, especially in the last 3 days.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, we found that DU20 and ST36 are frequently used acupuncture points for the treatment of ischemic cerebrovascular diseases [19]. Therefore, we selected these two acupoints as the targets of electroacupuncture in this experiment [18,20]. Our MWM results showed that the time it took for the electroacupuncture group to find a platform in the place navigation test was significantly shorter than that of the VaD group, especially in the last 3 days.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the number of Sirt1 positive cells in the hippocampal CA1 region and amygdala of the electroacupuncture group was significantly more than that of the VaD group, and the average gray value of Sirt1 was significantly lower than that of the VaD group. Through the results of westernt blot and immunohistochemistry experiments, we can conclude that electroacupuncture can reduce the inflammatory response in the brain tissue of VaD rats, and it may be mediated by regulating the Sirt1/STAT3 signaling pathway[18,23].…”
Section: Discussionmentioning
confidence: 99%
“…In the amygdala these cells develop during critical ages for amygdala-dependent adolescent socioemotional development 6,8,84 . Almost half of all lifetime mental health conditions onset during mid-teenage years 85 , and changes in amygdala volume and development are linked to social and emotional disorders 6,[86][87][88][89][90] . Connections between the unique trajectory of PL maturation and neuropsychiatric disorders are beginning to be explored, with some evidence for reduced maturation in MDD 46 (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%
“…NHPs may spontaneously present depression- and anxiety-like behaviors (Xu et al, 2015 ; Chu, 2019 ) but their detection depends on careful observation of a large population of animals. As a modeling alternative, disrupted husbandry or separation, either short or long-term, from either a parent or other social partner has been used to elicit a depressed- or anxious-like condition in both marmosets and macaques (Harlow and Suomi, 1971 ; Erickson et al, 2005 ; Winslow, 2005 ; O’Connor and Cameron, 2006 ; Spinelli et al, 2012 ; Zhang et al, 2016 ; French, 2019 ; Villard et al, 2021 ; Wood et al, 2021 ).…”
Section: Assessing Depression- and Anxiety-like Behaviors In Nhpsmentioning
confidence: 99%